Effectiveness of stem-based stad model in improving the understanding of science concepts - Djanurida Surjawati; Agung Purwanto; Iva Sarifah (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
This study aims to examine the effectiveness of the STEM-based Student Teams Achievement Division (STAD) cooperative learning model in enhancing elementary school students' understanding of science concepts. The research employed an experimental design using a pretest-posttest control group approach. The sample was selected through cluster random sampling. The research instrument consisted of a multiple-choice test designed to assess students' conceptual understanding of science, which was validated through tests of validity, reliability, item discrimination, and difficulty level. The results of the pretest homogeneity test confirmed that the initial abilities of both the experimental and control groups were equivalent, indicating that any observed differences in posttest scores could be attributed to the intervention. Further prerequisite testing showed that the posttest data were normally distributed and homogeneous, justifying the use of a parametric pooled-variance t-test. The analysis yielded a tcount of 5.38, which exceeded the ttable value of 1.99 at the 5% significance level, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). These findings demonstrate that the implementation of the STEM-based STAD model significantly improves students' conceptual understanding of science. Therefore, this instructional model can be considered an effective pedagogical strategy for enhancing the quality of science education in elementary schools.